Contrast-enhanced mammography in breast cancer screening: our experiences - Nićiforović , Dijana; Basta Nikolić, Marijana; Drvendžija, Zorka; Nikolić, Olivera; Mijatović, Aleksandra; Lukač, Sonja; Stojanović, Sanja (Vojnosanitetski pregled, 2025)
Background/Aim. Breast cancer is a leading global health concern. Contrast-enhanced mammography (CEM) presents a promising advancement in early breast cancer detection, excelling in sensitivity, specificity, and cost-effectiveness. The aim of the study was to assess the overall diagnostic efficacy of CEM in breast cancer screening, particularly in distinguishing benign from malignant lesions in dense breasts. Methods. A two-year retrospective study was conducted at the Center for Radiology, including a total of 279 women undergoing CEM following standard mammography. Results. CEM demonstrated high sensitivity (92.4%), specificity (75.1%), and a noteworthy negative predictive value of 97.0%, significantly reducing unnecessary biopsies. Conclusion. CEM is a valuable screening tool, offering enhanced diagnostic capabilities and the potential to reduce the number of unnecessary biopsies.  It is particularly beneficial for patients with dense breasts or inconclusive traditional mammography results.
Keywords: breast cancer; diagnosis; differential diagnosis; mammography; mass screening; sensitivity and specificity; ultrasonography, mammary.